Tax Planning Using the Fixed Asset Depreciation Method for Efficient Tax Payments at PT. Bina Dana Arta Insurance Tbk - Muhammad Dava Natawiria; Ida farida adi prawira; Memen Kustiawan (Jurnal Riset Perpajakan: Amnesty, 2024)
This research aims to evaluate tax planning using the fixed asset depreciation method for efficient tax payments at PT Tri Banyan Tirta Tbk. Quantitative research methods with a descriptive approach are used in the analysis, and the results show that the fixed asset depreciation method, especially the declining balance method, can increase the efficiency of income tax payments. The research was conducted at PT Tri Banyan Tirta Tbk, a bottled drinking water company. Taxes have a large contribution to Indonesia's state revenue, but are also a burden for companies. Therefore, tax planning, especially in choosing the method of depreciation of fixed assets, can influence the size of the tax burden and taxable profit. Fixed assets have an important role in company operations, and the depreciation process is applied systematically over their useful life. This research method analyzes PT Tri Banyan Tirta Tbk financial report data for 2021-2022. The results of calculating depreciation expense using the straight line and declining balance methods show that the declining balance method results in higher depreciation expenses, but results in lower income tax. Therefore, the conclusion of this research is that the declining balance method is more efficient in saving income tax payments for PT Tri Banyan Tirta Tbk.